An Analysis Imagery And Theme In The Poet I Wandered Lonely As A Cloud And The Solitary Reaper By William Wordsworth - Sukmawati (CV. Eureka Murakabi Abadi, 2022)
This research aims to determine what images and themes are contained in the poem I wandered lonely as a cloud and the solitary reaper by William Wordsworth. This research uses analysis descriptive qualitative method. The object and data source of this research is the poem I wandered lonely as a cloud and the solitary reaper by William Wordsworth which is taken from the website http: // poet.org> poems> william wordsworth which was published in 1815 and 1803 by using the solso theory. The results of study show that the poem I wandered lonely as a cloud consists of 4 stanzas and 24 lines, while in the solitary reaper poetry consists of 4 stanzas and 32 lines. There are three imagery contained in the first and second poetry, namely visual imagery, auditory imagery and kinesthetic imagery. The conclusion is that both of these poems have the same 3 imagery contained in them, namely visual imagery, auditory imagery and kinesthetic imagery where in the first poem the dominant imagery is visual imagery while in the second poem is auditory imagery, while on the theme of the two poems the researcher concludes that the author wrote these two poems on the same theme, namely nature.